Masked cognate translation priming with Arabic-English bilinguals: Further support for the morphological account - Alzahrani, Alhassan (East European Journal of Psycholinguistics, 2024)
The aim of this study is to test the two accounts that have been posited as how cognates are represented in the bilingual mind: the mophological account and the phonological account. More specifically, this study exploits the uique feature of pluralization in Arabic (i.e., concatenative vs. non-concatenative process of pluralization) to invetigate how cognates are represented in the bilingual mind of different-script bilinguals (Arabic-English bilinguals) using the masked priming technique. Two types of cognates were used: cognates that are pluralized concatenatively and cognates that pluralized non-concatenatively in Arabic. In concatenative pluralization, the phonology of the singualr form is intact such as هرمون /hormōn/ (hormone in English), which is pluralized as هرمونات/hormōnat/ (hormones in English). On the other hand, in non-concatenative pluralization, the phonology of the singular form is broken when a word is plualized non-concatenatively as in ترم /tirm/ (term in English) and أترام atrām/ (terms in English). The results show a comparable priming effect for both types of pluralizations indicating that cognates in Arabic-English bilinguals may have a shared morphological representation since the magnitude of priming was not affected by the type of pluralization. This similar priming effect for concatenative and non-concatenative pluralization indicates that cognates may share a special kind of morphological representation as suggested by the morphological account.Author: Alhassan Alzahrani 0000-0003-4547-6582 aajzahrani@bu.edu.sa